IbM Kelompok Usaha Rumah Tangga Aneka Keripik dan Sale Pisang Desa Wonodadi Kulon - I Made Kastiawan; Ismail .; Achmad Maqsudi (JPM17: Jurnal Pengabdian Masyarakat, 2014)
Abstract.Â Household Enterprises variety of chips made from cassava, sweet potatoes, bananas, taro and suweg and assorted tubers have grown in the village Wonodadi Kulon, District Ngadirojo, Pacitan, it is necessary to get a touch of appropriate technologies ( TTG ) to assist its production capacity. During this process still done manually with production capacity of about 20-30 packs per week for each craftsman. While the demand reached 30-50 packs per day. Similarly, the management system is carried out is still very simple, do not engage in the production of the records so it is not known whether profit or loss. This effort is still regarded as a sideline, so do not do it at the time rare spare time, but from the business side is very promising. Under these conditions, IBM team to try to help the mothers to provide some activities ie manufacturing machine (TTG) that capable to increase production capacity to 50 kg/h. Provide guidance on the management of the business so that the business of this chips can be one of the livelihood of the local women.Keywords: production capacity, TTG chips slicer materials, business management